Eras: is it possible to follow it in a tertiary government hospital set up? - Pattanayak, Sibaprashad; Maharana, Binoy Kumar; Behera, Manoj Kumar; Malla, Tapan Kumar; Kumar, Manish (International Surgery Journal, 2018)
Background: Fast-track surgery (enhanced recovery after surgery) is a set of protocols to reduce surgical trauma and postoperative stress by decreasing pain and complications, improving outcomes and decreasing length of hospital, while expediting recovery following elective procedures without an increase in complications or readmission. Methods: This was a prospective study over 2 years from March 2015 to February 2017 with 6 months follow up. 647 patients undergoing elective general surgery were followed up. Details regarding the age, sex, health status parameters and diagnosis collected. Preoperative evaluation, operative parameters and postoperative complications recorded. Post-operative course in hospital and any deviation of normal post-operative course and its management recorded and analyzed. Results: In government hospital (MKCG Medical College, Berhampur, Odisha), following ERAS protocol completely is impossible. But most protocols in preoperative, intraoperative, postoperative phases were followed, leading to early discharge of patients without any complications in most cases. In my study, drains were given in 157 cases, nasogastric tube in 89 abdominal surgeries. 129 cases were performed under general anaesthesia and 518 cases under spinal/epidural/mid thoracic epidural anaesthesia. 60 underwent overnight fasting. All received carbohydrate loading, antibiotic prophylaxis, thrombo-prophylaxis before surgery. Bowel preparation done in 50 abdominal surgeries. Conclusions: The study provided a strong evidence that ERAS is safe to practice in elective general surgeries. It is associated with decreased incidence of complications, significant reduction in duration of hospitalisation and reduction in overall morbidity and decreased rate of re-admission. Thus, improves patient’s compliance.